The discursive politics of climate change: risk, power and opportunities for democratization - Carvalho, Anabela (2019)
[Excerpt] The speed and scale of human impact on the planet have, in the last few decades, reached unprecedented levels. As the composition of the atmosphere itself is rapidly modified, climate change has become the most severe threat to both biophysical systems and human security, thus demanding a fundamental rethinking of its root causes. Despite much expectation regarding the Paris Accord and other developments, most socioeconomic practices and structures remain unchanged. In this short paper I will argue that, despite much focus on (inter)governmental policies in media(ted) discourses, climate change has been depoliticized in various ways, and that a radically democratic approach is needed to address it.